PENGARUH KUALITAS PELAYANAN, KEPUASAN NASABAH DAN KUALITAS PRODUK TERHADAP LOYALITAS NASABAH DI KANTOR CABANG BSI LANGSA DARUSSALAM - Ulil, Amri; Raihan (LPPM-UNIKI, 2024)
This research aims to provide empirical information by analyzing the influence of service quality, consumer satisfaction and product quality on customer loyalty at the BSI Langsa Darussalam Branch Office. The research method used is associative with a quantitative approach. The sample for this research was 193 BSI Langsa Darussalam Branch customers, using the Accidental Sampling technique. And data analysis for hypothesis testing uses path analysis. The results of the research are known; (1) there is a causal relationship between service quality variables and consumer satisfaction, consumer satisfaction and product quality, as well as product quality and service quality with an average of 0.372. (2) there is a direct and indirect influence of service quality on customer loyalty of 43.74%. (3) customer satisfaction has a direct and indirect influence on customer loyalty of 33.06%. (4) product quality has a direct and indirect influence on customer loyalty of 33.23%. (5) simultaneously service quality, customer satisfaction and product quality contribute to customer loyalty by 39.3%.